Production of chemicals using dynamic control of metabolic fluxes - Xu, Peng (Current opinion in biotechnology, 2018)
[Display omitted] •Engineered cell experiences metabolic imbalance with reduced fitness.•Overproduction phenotype requires dynamic redistribution of cellular resource.•Metabolite-responsive TFs rewired to sense the fluctuating environment.•Self-adaptive and autonomous control to achieve dynamic activity compensation.•Synchronize cell activity by engineering cheater-killer and quorum-sensing circuits. Engineered microbial cell factories are constantly experiencing metabolic imbalance due to nutrients depletion, metabolites buildup, evolutionary pressure or genetic instability. It is important to equip the engineered cell factory with sensor-regulator system to enable cell adjust metabolism and respond to the changing environment. Dynamically allocating cellular resources and optimally controlling pathway expression have proved as promising strategies to manage the tradeoff between cell growth and product formation as well as improve the cost-competitiveness of industrial fermentation. With metabolite-responsive transcriptional factors as basic tools, metabolic engineers are well positioned to engineer robust cell factories that achieve self-adaptation or autonomous control for both biotechnological and biomedical applications. In this review, we present promising dynamic control strategies that have been successfully applied to pathway optimization and chemical manufacturing.